Research progress on clinical application of fire dragon moxibustion (火龙灸临床应用的研究进展) - WANG Pu (王璞); WU Qiaomei (吴巧媚); LIU Yu (刘宇); XU Jianying (徐健莹); CHEN Lijia (陈莉佳); GUAN Lijuan (关丽娟) (中西医结合护理)
Fire dragon moxibustion, as one type of sandwiched moxibustion, has advantages of larger area of moxibustion, bigger moxa, stronger heating power and therapeutic effect compared with other types of moxibustion. The aim of this paper is to reviewed the studies about clinical application of fire dragon moxibustion, summarized the application mechanism and research status, find superiorities and principles of treatment on dominant diseases . (火龙灸为“隔物灸”中的一种灸法, 与其他灸法相比, 火龙灸具有施灸面广、艾柱大、火力足、温通力强等优点。本文通过对近年来火龙灸临床应用的论文进行分析、总结, 概述火龙灸疗法的临床应用机制与临床研究现状, 找寻火龙灸的优势病种, 并对火龙灸今后的研究进行展望。)